A Multimodal Analysis of Children’s Nutrition Advertisement - Nuryanti, Dewi (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2024)
The study aims at explaining the multimodal analysis in children’s nutrition advertisement. It is about what meaning can be conveyed through the advertisement’s signs as the combination of video, text, sounds, and others. The research is conducted by using descriptive qualitative method, in which the writer only explains all phenomena without using any number. In doing the analysis, the writer uses the theories of Systemic Functional Linguistics by (Halliday, 1994), theory by Anstey & Bull (2010) that focussed on modes in the video advertisement, and Multimodal theory by Kress & van Leeuwen’s (2001). The results have found that the new Nutrilon Royal advertisement has shown a good purpose of persuade its customers to think about giving good nutrition to their kids in early time. The use of the narrative with soft voice has caused the viewers to pay their attention to the advertisement. The use of video of children can be the evidence of how good the product is. The narrator speaks in a warm, encouraging tone, fostering trust, and emotional connection. The use of the certain words engages parents personally, implying that the new Nutrilon Royal plays a vital role in every child's development. The advertisement is structured to move smoothly from one scene to another, reflecting the continuity of a child’s growth journey. The combination of spoken narration, music, and visuals ensures cohesion, with each mode supporting the overarching message of healthy development starting with good nutrition.